Constitution in Power Dynamics: An Analysis of the Role and Implications in Indonesia - Mahmuda, Irma (Penerbit Mandalika Indonesia, 2024)
This study explores the role and implications of the constitution in the dynamics of power in Indonesia using a qualitative approach through literature studies and library research. The constitution serves as the supreme legal framework that regulates the structure, function, and limitations of state power. However, in practice, constitutional interpretation and implementation are often influenced by political interests, leading to shifts in governance dynamics. This research analyzes the interaction between the constitution and political power, highlighting its impact on democratic institutions, governance stability, and legal certainty. Through an in-depth examination of various legal documents, academic studies, and historical developments, this paper identifies key patterns in constitutional amendments, judicial review decisions, and executive-legislative relations. The findings indicate that while the Indonesian constitution provides a strong legal foundation for democratic governance, its application is frequently contested, particularly in relation to political maneuvering, institutional autonomy, and public participation. The study also reveals how constitutional amendments and judicial interventions have shaped the balance of power in Indonesia, both reinforcing and challenging democratic principles. This paper concludes that a dynamic and evolving constitutional framework is crucial to maintaining democratic integrity while adapting to socio-political changes. Ensuring transparency, accountability, and adherence to constitutional principles is essential for sustainable governance. By examining Indonesia’s constitutional dynamics, this study contributes to a broader understanding of the relationship between law and power in emerging democracies.